Educational Challenges in Underdeveloped Regions of China: A Microscopic Analysis of Current EFL Writing Pedagogies in a Chinese Normal College (International Journal of Language, Literacy and Translation, 2025)
This research is aimed at exploring unsustainable development in education in China’s underdeveloped regions from the micro perspective of the current state of EFL writing pedagogies in a Normal College in North-eastern China (namely Manchuria). It studies the current state of the teaching of EFL writing from the methodological, practice, and achievement aspects (students’ test performance). This paper also examined the existence of educational unsustainable development in this representative university in Manchuria from the micro perspective of the teaching of EFL writing. To fulfil the research objectives, quantitative analysis approaches were employed through an eight-question questionnaire. A total of 626 valid responses were collected with a response rate of 95.28%. Results indicated that unsustainable development in education does exists in this university in terms of EFL writing pedagogies covering both theoretical and practical aspects. The below-average teacher competence in this underdeveloped area and the educational inequality in terms of human resources were among the responses collected. The educational inequity and inequality in terms of educational environment and educational climate were also pointed out. Minimal and insignificant achievement of teaching was also evidenced in students’ low performance in CET4 Writing and Translation. Recommendations for further research were given.